An Analytic Study on the Effect of the Growth of the Economic Development and Communication and Information Technology on the Human Societies - Sahebzadeh, Mandana; ., . (International Journal of Engineering and Technology, 2018)
Parallel to economic development, Communication and information technology influences the different aspects of the human life. In many cases, this technology has worked very well to meet the needs of societies, but in other societies causes some problems. In this regard, some concepts is challenged by improving the economic development and Communication and information technology. some of which are â€œglobalization of economy, Communication and information technology, cybercrime, pornography and anti- cultural problems, digital gap, development the learning and teaching, new family problems, increase the public awareness, cultural relationships, digital wars, and interaction with meritâ€. This paper studies the analysis of the positive and negative effects of the rapid growth of economic development and Communication and information technology in the human societies.Â